Comparison between knowledge, behavior and risk perception about the STD/AIDS in medicine and law students from PUC-GO - Carneiro, Letícia Salles; Silva, Isadora Abrão; Ferreira, Denise Milioli (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: There has been a rise in the incidence of STIs/AIDS in the young Brazilian population; therefore, college students are a major focus for change of risky sexual behaviors. Objective: To analyze knowledge, sexual behavior, and risk perception of students in different years of the medical and law programs at the Pontifical Catholic University of Goiás (PUC-GO), Brazil, with regard to STIs/AIDS. Methods: Administration of anonymous questionnaires to students in their first, third, and last years of the medical and law programs at PUC-GO, using probability-proportional-to-size sampling and with margin of error set at 5%. Results: Medical students answered 201 questionnaires and law students 441 questionnaires. The comparison of both programs revealed that 40.3% of law students and 19.6% of medical students believe that HIV is transmitted through kissing and that 39.9% of law students and 29.3% of medical students believe that this virus is also transmitted through utensils. Consistent condom use was reported by 21.2% of medical students and 30.1% of law students. Medical students have greater risk perception of sexual behavior, and 83.8% claim they have been exposed to STIs; furthermore, 72.6% of law students believe they are at risk. Conclusion: There was an increase in medical students’ knowledge about STIs/AIDS throughout the program. Nevertheless, medical students adopt riskier sexual behavior, which is caused by the lower frequency of condom use. Medical students have, however, increased risk perception regarding sexual behavior.